Analysis of Driving Characteristic of Bistable Mechanism based on Dynamics - Meng Qingguo; Zhang Lili; Yang Xuefeng; Li Wei; Lu En; Dong Shi (Jixie chuandong)
A compliant bistable mechanism is a device that can maintain two distinct positions without power input. There is a wide range of applications in the field of MEMS and mechanical transmission. Usually,the energy method is used for judging the steady state of compliant mechanism,but the driving characteristic of compliant mechanism can’t be analyzed. A new method for the steady state analysis of four bar mechanism based on dynamics is presented to analyze the driving characteristic of four bar mechanism with only a compliant joint.And according to the drive characteristic curve,the steady state characteristics of the flexible mechanism are judged. Firstly,the pseudo- rigid body model of the compliant four bar mechanism is established by using pseudo- rigid body method,and the dynamic equations are listed by using the Lagrange equation of the second kind. The change curve of driving force is calculated when the active member is rotated 360°. Then the corresponding flexible four bar mechanism model is established in ADAMS,and the simulation results are compared with the results of the dynamics calculation to verify the accuracy of the dynamics model. Finally,a numerical example is given to compare the dynamics analysis method with the traditional energy method. The results show that the dynamics analysis method is effective. At the same time,the critical value of the driving force in the process of steady state and non steady state position conversion are obtained,and a new method for the design of the flexible steady state mechanism is provided. At the same time,based on the dynamics characteristic of bistable state,the bistable switches and sensor can be designed and used.